(3GdQSGdI GdOGeZI aj GdQO Ydi GdfUjQis - (3GdaGShGdfROs ((3MeRI Hf Ydi Hf CMeO s)
(3ChdgG (B:s
(3CeG HYO CjOce Gdehdi HJCjjOg Efg hQO Edj cJGHkG Cdag HYV GdfUjQjI GdcGaQjf hSeGg cJGH GdMbGFb hcTa GdeMLhH s
(3BNQgG (B:s
(3hGdMeO dehdGfG hMOg aj GdSQGA hGdVQGA JeJ HMeO ehdGfG hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3QO GdeDda ai gPg GdQSGdI Ydi cJGH GdMbGFb hcTa GdeMLhH dCMO GdfUjQjIs
(3QSGdI ef QSGFd GdOQhRs
(3JHUQI GdYfhGf (B:s
(3JYbjHs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds